Black Scoter habitat use along the southeastern coast of the United States. Issue 16 (27th July 2021) - Plumpton, Hannah M.; Silverman, Emily D.; Ross, Beth E.
Abstract: While the Atlantic Coast of the United States and Canada is a major wintering area for sea ducks, knowledge about their wintering habitat use is relatively limited. Black Scoters have a broad wintering distribution and are the only open water species of sea duck that is abundant along the southeastern coast of the United States. Our study identified variables that affected Black Scoter ( Melanitta americana ) distribution and abundance in the Atlantic Ocean along the southeastern coast of the United States. We used aerial survey data from 2009 to 2012 provided by the United States Fish and Wildlife Service to identify variables that influenced Black Scoter distribution. We used indicator variable selection to evaluate relationships between Black Scoter habitat use and a variety of broad‐ and fine‐scale oceanographic and weather variables. Average time between waves, ocean floor slope, and the interaction of bathymetry and distance to shore had the strongest association with southeastern Black Scoter distribution. Abstract : Our study identified variables that had the most influence on Black Scoter distribution in the Atlantic Ocean along the southeastern coast of the United States. We used variable selection to evaluate relationships between Black Scoter habitat use and a variety of broad‐ and fine‐scale oceanographic and weather variables.